Manajemen Pengembangan Madrasah - Siti Nurhidayatul Hasanah (Jurnal Kependidikan Islam, 2012)
Effort developmentaling to islamic middle school shall do komprehensial, integral and sistemik. All component and aught elements in education system shall at diagnosis and looked for by its doctor, one that gets bearing with things that its philosophical character, structural up until its operational Hereafter structural ala, in the reference islamic middle school shall perpetually be beavered that get same rights rights in national education system. And operational problem, this perhaps that important, development in this case available four thing who shall be noticed, which is; First, shall mark sense sharpness among which aspired by its operational stage; both of, empowerment (empowering aught institute with set its system back third, fixed up, update, and management system development or management, and fourth, take step-up needful man.